Improved community-led water governance approach in Bangladesh - CGIAR Research Program on Rice (2019)
The improved sluice gate management synchronized with crop management was piloted. This pilot was also used to provide training to 290 stakeholders on improved water management (mainly drainage) for intensifying the production system.